(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In India, women’s lower social position is frequently blamed on the ineffectiveness and inadequacy of existing legislation. Even if this is a recurring issue, the relationship between legislation and the treatment of women remains the most important component. Women’s Inheritance rights are still viewed in a feudal context, and numerous gender-biased legal provisions fail to offer equal access to economic resources despite the Constitutional guarantee of equality. A shift in perspective is needed to better comprehend what motivates anti-feminist laws and how they keep women economically dependent on their male counterparts. An analysis of the function of legislation in defining women’s Inheritance rights in India serves as an example of this economic dependency. With a focus on Hindu and Muslim law, this study aimed to examine and assess the position of women in relation to their Inheritance rights under various personal laws. Law and women’s economic standing are examined, as well as the areas that need to be prioritised for comprehensive legislations, such as in the subject of marriage Inheritance law in India, in this study. Present law, while legally granting equal social standing to women, also restricts their potential growth by preserving patriarchal practises, which denies women access to economic resources outside the home and provides an inequitable division of Inheritance within the family.